2022
DOI: 10.3390/jcm11102904
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Handgrip Strength Is Associated with Lower Cognitive Performance in the Elderly

Abstract: (1) Background: Several studies have reported that handgrip strength (HGS) may be a sign of lower cognitive performance. However, studies supporting an association between asymmetrical HGS and cognitive function are lacking. This study aimed to determine the association between asymmetrical HGS and cognitive performance among the elderly. (2) Methods: The study sample included 2729 individuals aged ≥60 years-old who participated in the 2011–2014 National Health and Nutrition Examination Survey. The cognitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The results show that lower cognitive performance in the elderly is associated with handgrip strength. (69) The results of this study are in accordance with research in Russia which demonstrated that handgrip strength is associated with a high risk of malnutrition, low autonomy, decreased physical and mental function, and risk of death over the next five years. (70) It has been demonstrated that skilled hand movements and control of handgrip strength involve not only cortical motor areas but also higher cognitive performance.…”
Section: Handgrip Strength and Cognitive Functionsupporting
confidence: 90%
“…The results show that lower cognitive performance in the elderly is associated with handgrip strength. (69) The results of this study are in accordance with research in Russia which demonstrated that handgrip strength is associated with a high risk of malnutrition, low autonomy, decreased physical and mental function, and risk of death over the next five years. (70) It has been demonstrated that skilled hand movements and control of handgrip strength involve not only cortical motor areas but also higher cognitive performance.…”
Section: Handgrip Strength and Cognitive Functionsupporting
confidence: 90%
“…Both of these HGS calculation methods have been used across different studies [ 9 , 11 , 14 , 15 ]. For example, to explore the association between HGS asymmetry and cognitive performance in older adults, a recent study enrolled 2729 Americans over 60 years of age and adopted the average HGS method [ 14 ], while an earlier study enrolled 17,163 Americans over 65 years of age and used the maximal HGS method [ 11 ]. Notably, the effect of this choice between the use of maximal or average HGS values on HGS asymmetry remains unknown.…”
Section: Introductionmentioning
confidence: 99%